IMPLEMENTATION OF THE LEVY POLICY FOR FOREIGN TOURISTS FOR THE PROTECTION OF BALI'S CULTURE AND NATURAL ENVIRONMENT - Rimbawan, I Putu Dedy; Putra, I Made Luhur Adi (Jurnal Ilmiah Cakrawarti, 2025)
Bali Island, as an international tourist destination, is known for its natural beauty and cultural richness. However, the increasing number of foreign tourists poses significant challenges to the preservation of culture and the environment. To address this issue, the Bali Provincial Government has implemented a levy policy for foreign tourists, regulated by Bali Regional Regulation Number 6 of 2023 concerning Tourist Contributions for the Protection of Bali's Natural Environment and Culture. This policy aims to collect funds allocated for the protection of local culture and environmental preservation. This research aims to analyze the implementation of the levy policy and assess its impact on Balinese culture and environment. The research method used is a qualitative descriptive approach, with data collection through interviews, observations, and documentation studies. Interviews were conducted with various stakeholders, such as local government, tourism managers, traditional leaders, and foreign tourists. The data obtained were analyzed using thematic analysis techniques to identify challenges and opportunities in the implementation of this policy. Research results indicate that the levy policy based on Bali Regional Regulation Number 6 of 2023 has great potential in supporting the preservation of culture and the environment. However, several key challenges in the implementation of this policy include a lack of understanding among tourists, suboptimal fund management, and the need to enhance local community involvement. To enhance the effectiveness of this policy, more intensive socialization to foreign tourists, more transparent fund management, and active participation from the Balinese community are needed.